Design considerations in shaping the identity of architectural components towards forestry research and education - Jaafar, Nor Syuriaty (2022)
The development of Research and Education Forests (REF) in Malaysia is a complement to the ongoing efforts on the importance of conserving the natural forests which are a treasure of natural heritage for the country, as well as the world. REF functions as a natural forest-based learning, research and development that requires the facilities in accordance to the sensitivity of the forest ecosystem. Therefore, architectural components that are in harmony with natural forest environment is needed not only to create sustainable REF development, but as a source of inspiration of the local identity. A strong identity is a need to establish citizen’s self-esteem and without it all, development efforts are seen as having no purpose, so that it would not be a catalyst for the country's progression. Studies related to identity formation with regard to architectural design in the REF have not yet been specifically explained. Hence, this study aims to investigate the relationship between the architectural design aspects and the harmonization with natural forest environment to determine design considerations in shaping the identity of architectural components within the REF. The mixed method approach was used in the research methodology and results were validated through triangulation which involved the reviewed data from selected literature and case studies. The literature review covers the constructs of Research and Education Forest (REF), design harmonization and architectural identity. Subsequently, the case study was selected at Sultan Idris Shah Forest Education Centre (SISFEC), consisting site observation and survey questionnaire. The survey was based on the user’s perception to the design harmonization with the natural forest environment and the place identity. Data on the design harmonization were analysed using SPSS 21, where the Pearson Correlation revealed that all selected design aspects are correlated positively to the harmonization of the architectural components with natural forest environment. Later, the Regression Analysis verified the proposed model statistically and proved that harmonize design aspects had significantly increased the design harmonization with forest environment for the formation of architectural identity. Furthermore, Thematic Analysis on the place attachment showed that place identity is influenced by the uniqueness of nature, activities related to the forest environment and cultural uniqueness. Results of triangulation emphasized that the four (4) main design considerations in shaping architectural identity which must be taken into account by all stakeholders, namely spatial organization, the appearance of forms, the essence & ability of material and the style of design. The findings of this study would be able to assist designers in creating a sustainable REF with architectural identity that could help manifest the global obligation in preserving the world natural heritage, as well as showcasing its distinguished national cultural heritage.